Perceptions of global coronary heart disease risk, and adherence to antihypertensive treatment among low income urban women in Delhi, India - Dhar, Lipi (Curtin University, 2016)
This study examined perceived coronary heart disease (CHD) risks and adherence to antihypertensive treatment among women in a low-income area in Delhi, India. A mixed-methods design comprising a structured survey and semi-structured interviews was used. Among findings, most participants inaccurately perceived their CHD risks, with poor adherence to antihypertensive treatment. The findings can help inform the design of interventions to improve women’s accuracy of their perceived CHD risk and medication adherence to prevent CHD.